Size composition, growth, mortality and yield of Alectis alexandrinus (Geoffory Saint -Hilaire) in Bonny River, Niger Delta, Nigeria - S. N. Deekae; K. O. Chukwu; A. J. Gbulubo (Advances in Aquaculture and Fisheries Management, 2022)
A twelve month study on the size composition, growth, mortality and yield of Alectis alexandrinus revealed a length range of 11.5 - 33.8 cm (standard length) . Employing the length frequency method in the FISAT II package gave the following results for the Von Bertanlanffy growth parameters: L = 35.23, K = 0.680, to = 0.3214 and = 2.926. The total mortality (Z) was 2.47, natural mortality (M) 1.39 and fishing mortality (F) 1.08.The relative biomass per recruit (knife edge selection) was Lc/ L = 0.05, E10 = 0.355 and E50 = 0.278. Although the exploitation rate (E) was 0.44 the Emax was 0.421 indicating moderate exploitation of the fish in Bonny River. There is room for increased effort in the fisheries.